The Effect of Herbal Medicine Mixture and Indigestion to Karapan Sapi in Sampang Regency in 2021 - Yulianti Mauludy Utami; Nusdianto Triakoso; Tjuk Imam Restiadi; Mirni Lamid; Wiwik Misaco Yuniarti; Sunaryo Hadi Warsito (Jurnal Agro Veteriner, 2024)
This study aims to find out the effect of giving mixed ingredients to indigestion to Karapan Sapi on Sampang Regency in 2021. This research began in January 2021 to February 2021 in Sampang Regency, East Java. The sample used in this study is a Karapan Sapi that giving mixes ingredients (plam wine, wine fermentation, or beer) into its drink in Sampang Regency. The tool used in this study is a questionnaire by conducting interviews to study respondents, namely 20 owners of Karapan Sapi. Data grouped by mixed ingredients they use and dose of the mixed ingredients and then analyzed using the Chi-Square method to determine the effect of the mixture and the dose of the ingredients with indigestion. The results of the analysis showed that the mixed ingredients showed a noticeable influence (p<0.05). The results of the analysis of the dose of the ingredients also showed that the dose of the material showed a real influence (p<0.05). Based on the results of the analysis, it can be concluded that the provision of mixed ingredients and their doses affect the indigestion in Karapan Sapi in Sampang Regency.